Konsep Pengembangan Kawasan Wisata Tirta Mbelong - Mohammad Reza; Maria Christina Endarwati; Annisa Hammidah Imaduddina; Fardiah Qonita Ummi Naila (Sustainable, Planning and Culture (SPACE) : Jurnal Perencanaan Wilayah dan Kota, 2022)
In the western part of Malang district, precisely in the Tajinan sub-district, it has hidden tourism potential. In the eastern part of the Tajinan sub-district, it has tourism potential to be developed in the form of a swamp area. Opportunities to take advantage of the beautiful scenery as well as the development of water-based tourism and culture in this area are still wide open to be maximized and have not been implemented optimally. In addition, this development opportunity is encouraged by the government with the allocation of village funds. Villages are also directed to be able to develop their potential for the sake of increasing mutual welfare. Seeing this opportunity, the potential for tourism development in villages should get more attention, especially for its sustainability in the long term. The purpose of this research is to identify the potential and opportunities for planning the Mbelong Tourism area, Jatisari as an Education-based Fisheries Agrotourism concept and to formulate a development plan for the Fisheries Agrotourism area in Jatisari Village, Tajinan District, Malang Regency. This type of research is a qualitative research. The concept of Tirtha Mbelong Tourism is based on the existing conditions of tourist attractions which are areas that store air so that this tourist spot has several large pools that have the potential to be used as attractive tourist attractions.